Character Building Training untuk Membentuk Karakter Santri di Pondok Pesantren Sunan Drajat Lamongan - Hasanah, Muhimmatul; Musbikhin (Proceedings of Annual Conference on Community Engagement, 2022)
Moral-based education, commonly known as character building, is an effective solution to the problems of today’s nation’s moral decadence. Moral-based character education is expected to be an innovation to restore the spirit of education that has been distorted and create academic people who are intellectually, emotionally, morally, socially, culturally and spiritually intelligent. The goal to be achieved is how to build the character of students through a training mechanism based on Islamic and cultural values, both intellectual, emotional, moral, social and spiritual aspects. The service learning method is an option that involves students, institutions and communities with the aim of each being able to benefit from it. From the results found in the field, students will understand their relationship with God; self-relation with oneself; self-relation with others; relationship with the environment. Character Building training with an emotional and spiritual intelligence approach, leads the trainees to destroy mental barriers and technical barriers in achieving success, so that their potential and strengths can be optimized to achieve their dreams and goals.